Species checklist of wild orchids at Sungai Rawog Conservation Area - Siti Fatimah Md.-Isa; Ahmad Asnawi Mus; Mohd Gan Abdul Rashid; Franey Joseph Chong; Edward Entalai Besi; Debbie anak Sandin (Sabah Forestry Department, 2024)
The valley of Rawog river is one of the protected compartments areas that serve as safeguarding areas for wildlife corridor connecting Deramakot Forest Reserve and adjacent oil palm plantations. The result from Sungai Rawog Conservation Area (SRCA) Scientific Expedition ver 2.0 will be used as comparison data with previous expedition version 1.0 conducted five years ago. However, the documentation focus on wild orchid in the Rawog valley is first documented here. In this report, we listed orchid species found during the fourday expedition at seven different trails. In total, we identified 17 orchid species including one leafless myco-heterotrophs species, Lecanorchis multiflora J.J.Sm. All the identified species were further classified into two subfamilies: Epidendroideae and Vanilloideae with 16 species belonging to Epidendroideae and one species belonging to Vanilloideae. Although this data is based on only a four-day survey, orchids in the study area are not peculiar compared to other lowland forest areas that have been logged. Besides, the number of epiphytic orchid species is higher than terrestrial orchid species in the surveyed area. This basic information is very important and could contribute to understanding the species and the surrounding ecosystems. However, more details on ecology of the species are needed to make better comparisons among other protected compartment areas in The Segaliud Lokan Forest Reserve.